DISTANCE EDUCATION IN HISTORICAL ASPECT - Katane, Irena; Katans, Edgars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In this article the authors give theoretical substantiation to the ideas of distance education, as well as offer an insight into the development of distance education, where the experience of many countries is summarized. The aim of the article is to publish the results of the theoretical research on the history of distance Education. As a result of research, the authors drew several conclusions: 1) since the 18th century, when the first attempt of distance education had been registered, till nowadays the humankind has amassed rich experience in this sphere;2) the correspondence education is the initial form of distance learning; 3) the development of distance education in the 20th century was facilitated by the development of information and communication technologies and their introduction into education; 4) in connection with the development of distance education, a new direction — media pedagogy — began its development in pedagogy.